Analisis Semiotika Makna Budaya dalam Iklan Djarum 76 Edisi Dirgahayu Indonesia - Adrya, M. Rifqi; Azhar, Anang Anas (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze how the Djarum 76 Dirgahayu Indonesia Edition advertisement reflects Indonesia’s cultural values and national identity. The research employs a qualitative descriptive method, utilizing Roland Barthes’ semiotic approach to interpret the denotations, connotations, and myths present in the advertisement’s symbols.The analysis reveals six dominant cultural representations in the advertisement: Batik motifs,Papuan dance,Madurese pencak silat,Payung dance,Plate dance,Kacet Papatai dance.These findings indicate that the Djarum 76 Dirgahayu Indonesia Edition advertisement uses diverse traditional cultural elements to reinforce messages of nationalism and pride in Indonesia’s cultural heritage. Overall, the advertisement presents a narrative of Indonesian national identity through symbols of traditional culture that are rich in meaning. This semiotic analysis demonstrates that the visual elements are not merely aesthetic decoration; rather, they serve as communicative tools for conveying cultural values and national pride. Through these findings, this study is expected to enrich the understanding of how cultural meaning and national identity are constructed in the context of commercial promotional media.